Insurance impacts survival for children, adolescents, and young adults with bone and soft tissue sarcomas. (15th December 2019) - Penumarthy, Neela L.; Goldsby, Robert E.; Shiboski, Stephen C.; Wustrack, Rosanna; Murphy, Patricia; Winestone, Lena E.
Abstract: Background: While racial/ethnic survival disparities have been described in pediatric oncology, the impact of income has not been extensively explored. We analyzed how public insurance influences 5‐year overall survival (OS) in young patients with sarcomas. Methods: The University of California San Francisco Cancer Registry was used to identify patients aged 0‐39 diagnosed with bone or soft tissue sarcomas between 2000 and 2015. Low‐income patients were defined as those with no insurance or Medicaid, a means‐tested form of public insurance. Survival curves were computed using the Kaplan‐Meier method and compared using log‐rank tests and Cox models. Causal mediation was used to assess whether the association between public insurance and mortality is mediated by metastatic disease. Results: Of 1106 patients, 39% patients were classified as low‐income. Low‐income patients were more likely to be racial/ethnic minorities and to present with metastatic disease (OR 1.96, 95% CI 1.35‐2.86). Low‐income patients had significantly worse OS (61% vs 71%). Age at diagnosis and extent of disease at diagnosis were also independent predictors of OS. When stratified by extent of disease, low‐income patients consistently had significantly worse OS (localized: 78% vs 84%, regional: 64% vs 73%, metastatic: 23% vs 30%, respectively). Mediation analysis indicated that metastatic disease at diagnosis mediated 15% of the effect of public insurance on OS. Conclusions: Low‐income patients with bone and soft tissue sarcomas had decreased OS regardless of disease stage at presentation. The mechanism by which insurance status impacts survival requires additional investigation, but may be through reduced access to care. Abstract : Low‐income patients with bone and soft tissue sarcomas had decreased overall survival compared to patients with private insurance regardless of disease stage at presentation. This survival disparity is partially mediated by presentation with advanced disease.